Analisis Buku Ajar Tematik Kurikulum 2013 Edisi Revisi Tahun 2017 Pada Aspek Scientific Approach Di Kelas II Pada Tema II “Bermain di Lingkunganku” - Dani, Adian; Mufarizuddin, Mufarizuddin; Zulhendri , Zulhendri (Indonesian Research Journal on Education, 2021)
This study aims to determine the content of the 2013 curriculum thematic textbook revised edition 2017 the aspects of observing, asking, trying, reasoning, and communicating in second years on theme II "Playing in my neighborhood". This research is descriptive with a library research approach which aims to provide a systematic description of the ongoing situation in the research object, namely the analysis of the2013curriculum thematic textbook revised edition 2017 on the scientific approach in second years on theme II "Playing in my environment". Based on the results of the research related to the 2013 thematic curriculum textbook revised edition 2017 on the scientific approach in second years on theme II "Playing in my environment", it was concluded that: in my environment "based on the results of the research, on the aspect of observing, it was found that there were 113 activities that instructed students to observe. The content of the 2013 thematic curriculum textbook revised edition 2017 on the questioning aspect in second years on theme II "Playing in my neighborhood" based on the research results, on the questioning aspect, it was found that there were 53 activities that provided student activities to ask questions. How is the content of the 2013thematic curriculum textbook revised edition 2017 on the aspect of trying in second years on theme II "Playing in my neighborhood" Based on the results of the research, in the aspect of trying, it was found that there were 142 activities that required trying activities. The content of the 2013 curriculum thematic textbook reviced edition 2017 on the aspect of reasoning in second years on theme II "Playing in my environment" based on the results of the research, in the aspect of reasoning, it was found that there were 113 activities that instructed students to reason and 68 aspects of communicating.